Serum mineral levels at pregnancy and postpartum in single and twin pregnant sheep - Yildiz, A; Balikci, E; Gurdogan, F (Humana Press Inc, 2005)
This study was performed to investigate calcium (Ca), inorganic phosphorus (P), potassium (K), magnesium (Mg), and chlorine (0) levels in blood serum at d 60, 100, and 150 of gestation and at d 45 after parturition and to find out the significance of differences for macromineral levels during these stages of single or twin gestation in Akkaraman sheep. Blood samples of 30 apparently healthy pregnant Akkaraman sheep (15 single pregnancies, 15 twin pregnancies) were used. The samples were analyzed using a biochemical analyzer for Ca, P, Na, K, and Mg concentrations and using the Schales method for Cl levels. A statistically significant decrease (p < 0.001 and p < 0.05) was found on d 100 of pregnancy for Ca levels and for serum inorganic P levels in both groups. Twin pregnant sheep were found to have lower (p < 0.05) serum Ca and inorganic P levels than sheep pregnant with one fetus on d 100 and 150. Significant decreases (p > 0.05, p < 0.01) for serum Mg levels in both groups were recorded on d 100 and 150 of pregnancy. There were significant increases (p < 0.01) in serum Cl levels on d 100 in single and twin pregnant sheep.
Keywords: pregnancy; elements; sheep; twin; serum